The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1111/j.1525-1594.1989.tb02851.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Hemodialysis Center Water and Dialysate: Are Current Assays Adequate?

Abstract: Many dialysis centers depend on clinical laboratories or a commercially available dip culture to determine the contamination levels in water and dialysate. To determine whether these standard clinical culture procedures adequately quantitate bacterial contamination in hemodialysis center water and dialysate, test results of two routine clinical media was compared, trypticase soy agar (TSA) and plate count agar (PCA), with those of nutrient-poor R2A medium. Dialysate samples demonstrated significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 2 publications
1
11
1
Order By: Relevance
“…Nutrient-rich media tend to underestimate the bacterial contamination of purified water and dialysate fluids as observed in previous studies [1][2][3][4]. Hardinget al [I] reported that elevated temperature tends to produce lower colony counts than lower temperatures.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Nutrient-rich media tend to underestimate the bacterial contamination of purified water and dialysate fluids as observed in previous studies [1][2][3][4]. Hardinget al [I] reported that elevated temperature tends to produce lower colony counts than lower temperatures.…”
Section: Introductionmentioning
confidence: 57%
“…As observed previously [1], it is difficult to perform quantitative assays on isolates due to laboratory adaptation of the organisms. This assay, however, establishes that the same organisms may produce observ able colonies at different rates and that some organisms fail to grow at all on TSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium used, plate count agar, could have caused less bacterial growth compared with other media such as trypticase soy agar and nutrient-poor R2A medium (R2A) rec ommended by a few authors for dialysis fluid examination [5,6,18]. However, in a recent comparison between plate count agar and R2A.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, bacterial growth of dialysate samples in standard culture media, trypticase soy agar or plate count agar, was com pared to results obtained in a nutrient poor R2A medium, cultured at 25 °C for 96 h [79]. Several typical water bac teria grew better or more selectively on R2A agar.…”
Section: Microbiologie Monitoringmentioning
confidence: 99%